2020
DOI: 10.1002/chem.202002041
|View full text |Cite
|
Sign up to set email alerts
|

Biohybrid Conjugated Polymer Materials for Augmenting Energy Conversion of Bioelectrochemical Systems

Abstract: Bioelectrochemical systems(BESs) providef avorable opportunities for the sustainable conversion of energy from biological metabolism.B iological photovoltaics (BPVs) and microbial fuel cells(MFCs) respectively realize the conversion of renewable solar energy and bioenergy into electrical energy by utilizing electroactive biological extracellular electron transfer,however,alongwith this energy conversion progress, relativelyp oord urability and low output performance are challenges as well as opportunities. Adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Consequently, PFTP with these optical features could enhance the utilization of green light and improve the photosynthetic efficiency. 35 Meanwhile, the red band edges of green PC hydrogel and red PC hydrogel matched the absorption and emission peaks of PFTP, respectively. Therefore, this wavelength conversion performance of PFTP could be further enhanced by a slow photon effect.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Consequently, PFTP with these optical features could enhance the utilization of green light and improve the photosynthetic efficiency. 35 Meanwhile, the red band edges of green PC hydrogel and red PC hydrogel matched the absorption and emission peaks of PFTP, respectively. Therefore, this wavelength conversion performance of PFTP could be further enhanced by a slow photon effect.…”
Section: Resultsmentioning
confidence: 83%
“…Note that the absorption wavelength of PFTP (peaks at 370 and 560 nm) was complementary to that of photosynthetic pigments, and its emission wavelength (peak at 685 nm) overlapped with the absorption wavelength of photosynthetic pigments (Figure b). Consequently, PFTP with these optical features could enhance the utilization of green light and improve the photosynthetic efficiency . Meanwhile, the red band edges of green PC hydrogel and red PC hydrogel matched the absorption and emission peaks of PFTP, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Their absorption wavelength ranges are 700–1000 and 450–550 nm, respectively. By combining the polymer blend poly­(9,9-dioctylfluorenyl-2,7-diyl)–poly­(2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene) with the light-harvesting complex of Rhodopseudomonas palustris ( R. palustris ), Cogdell et al found that the fluorescence lifetime of the CP was decreased by 30% and efficient energy transfer from the CP to purple bacteria occurred . Our collaborator Xing et al assembled R. palustris with CPNs functionalized with cell penetrating peptide TAT (CPN-TAT) to increase photosynthetic efficiency (Figure a) .…”
Section: Conjugated Polymers Augmenting Natural Photosynthesismentioning
confidence: 99%
“…But they are constantly faced with the problem of limited PAR range of photosynthetic pigments. In addition, the compatibility of the formed biologic–electrode interface is a key factor affecting device efficiency . Therefore, improving light-harvesting efficiency and surface contacts is critical for constructing BPVs with excellent performance.…”
Section: Conjugated Polymers Augmenting Artificial Photosynthesismentioning
confidence: 99%
See 1 more Smart Citation